Non-invasive electroencephalogram-based anesthesiological monitoring in geriatric patients in the ent-surgery - Medhat H. Altoufaili; Tatiana V. Klypa; Irina A. Mandel; Maria S. Orekhova (Клиническая практика)
BACKGROUND: Demographic ageing of the society and the growing demand for medical service among the elderly citizens require perfecting the anesthesiology approaches. AIM: Evaluation of the efficiency of using various types of electroencephalography-based monitoring when performing general anesthesia in the settings of ENT-surgery in geriatric patients. METHODS: The randomized study included 99 patients (70–85 years old, ASA III–IV) who underwent surgery under general anesthesia for ENT pathology. The patients were distributed into three groups: Group A (n=33) — anesthesia controlled by CONOX — monitoring, Group В (n=33) — no cerebral monitoring, Group C (n=33) — controlled by BIS monitoring. The controlled parameters included the dosage of the medicinal products (Propofol, Fentanyl, Sevoflurane), the hemodynamics, the rates of intraoperative awakenings, postoperative nausea and vomiting, the need for additional pain medications and the parameters of the cognitive functions before and after surgery. RESULTS: The Propofol dosage in Group B was higher than in Groups А and С (p=0.016 and p=0.012 respectively). The concentration of Sevoflurane in Group С was lower (p=0.016), than in Groups А and В. Hemodynamic disorders and postoperative nausea/vomiting were more often observed in group В. Intraoperative awakenings were reported in 3% of the patients in Group А, in 9% for Group В and in 6% patients in Group С. Additional pain management was required in 39% of the patients in Groups А and В along with 42% in Group С, no statistical difference was found between the groups. Cognitive functions were better preserved in Group А with the duration of general anesthesia being more than 120 minutes (p=0.044). CONCLUSION: Anesthesiology monitoring based on electroencephalogram parameters, optimizing the dosages of the medicinal agents, decreases the rates of hemodynamic disorders, of intraoperative awakenings and of postoperative nausea and vomiting. Combined with the clinical monitoring of the electroencephalogram parameters, this accelerates rehabilitation and improves the surgery outcomes. The optimization of the dosage of opioids with controlling the anesthesia depth index (the Nociception Index, qNOX) positively affects the postoperative cognitive status of the patients.